Pesan Dakwah Hasan Al-Banna dalam Buku Majmu’at al-Rasail - Fuadi, M. Hanif (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2017)
This article analyzes the message of Hasan al-Banna's preaching in the book Majmu'at al-Rasail relating to the aqeedah, sharia and morals. The study used critical discouse analysis method of Norman Fairclough with an emphasis on the background of the social situation until the message of da'wah was formulated. The results of the research show that the message of da'wah in the book Majmu'at al-Rasail can be explained, among others: the message of the faith in theological discourse, the message of sharia in the discourse of power and the moral message in the discourse of social relations. The monotheistic belief system must be able to provide the divine spirit in all dimensions of life. This spirit grows out of true, pure, clean faith from the element of shirk to God; the sharia system requires applicable law according to the teachings of Islam, focusing on a number of social and political problems that hit the country of Egypt after the destruction of the Ottoman Caliph which fell into British hands. The message of Hasan al-Banna's preaching was oriented towards reforming the living system which was damaged by colonialism and desirous of returning it to the Islamic system. Artikel ini menganalisis pesan dakwah Hasan al-Banna dalam buku Majmuâ€™at al-Rasail yang berkaitan dengan akidah, syariah dan akhlak. Penelitian menggunakan metode analisis wacana kritis Norman Fairclough dengan penekanan pada latar situasi sosial sampai pesan dakwah terumuskan. Hasil penelitian menunjukkan pesan dakwah dalam Â buku Majmuâ€™at al-Rasail dapatÂ dijelaskan antara lain: pesan akidah dalam wacana teologi, pesan syariah dalam wacana kekuasaan dan pesan akhlak dalam wacana relasi sosial. Sistem keyakinan tauhid harus mampu memberikan semangat ketuhanan dalam segenap dimensi kehidupan. Semangat tersebut tumbuh dari akidah yang benar, murni, bersih dari unsur syirik kepada Allah; sistem syariah menghendaki hukum yang berlaku sesuai ajaran Islam, fokus pada sejumlah permasalahan sosial dan politik yang melanda negeri Mesir pasca kehancuran Khalifah Utsmaniyah yang jatuh ke tangan Inggris. Pesan dakwah Hasan al-Banna berorientasi pada pembenahan sistem kehidupan yang rusak karena penjajahan dan berhasrat mengembalikannya pada sistem Islam.